Characterization And Properties Of Natural Rubber/Recycled Acrylonitrile-Butadiene Rubber Blends - Ahmad @ Sofa, Hazwani Syaza (2018)
In this study, five series of formulations have been used to study the effects of recycled acrylonitrile-butadiene rubber glove (NBRr) blending together with natural rubber (NR). Cure characteristics, tensile test, hardness and resilience tests, crosslink density test, fatigue test, thermal analysis, and Fourier transform infrared (FTIR) analysis were carried out on these five series. Morphology of failure surface was analyzed using Scanning electron microscopy (SEM). In the first series, natural rubber/virgin acrylonitrile-butadiene rubber (NR/NBRv) blends showed better cure characteristics and mechanical properties compared with NR/NBRr blends. However, NR/NBRr blends showed a better result on some properties such as higher modulus and hardness, and less solvent uptake. ENR-50 and EVA was added into the NR/NBRr blends as compatibilizers in the second and third series. Result indicated cure characteristics and mechanical properties of compatibilized NR/NBRr blends were improved compared with uncompatibilized NR/NBRr blends. However, addition of ENR-50 into NR/NBRr blends showed better cure characteristics and mechanical properties in terms of scorch time, tensile strength, modulus, hardness, and solvent uptake compared with NR/NBRr blends with EVA. It had been proven by SEM micrograph of failure surface which shown addition of compatibilizer enhanced the compatibility of NR/NBRr blends. Further study of ENR-50/NBRr blends was carried out in the fourth series. Results show that cure characteristics and mechanical properties improved for all blends compared with NR/NBRr blends. Blending ENR-50 with NBRr gives better compatibility and strong interfacial adhesion between ENR-50 and NBRr. On the fifth series the effects of different crosslinking system which are sulphur (S), dicumyl peroxide (DCP), and mixed system (S+DCP) on NR/NBRr blends were carried out. The sulphur system show the best cure characteristics compared to peroxide and mixed systems, while the mixed system show the best mechanical and physical properties compared to sulphur and peroxide systems at all blend ratios.